(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The study aimed to analyze the impact of digital transformation on achieving development goals in the government sector in the Kingdom of Saudi Arabia, in accordance with the Kingdom’s Vision 2030. The study population included government sector workers, and a random sample of 258 individuals from various departments and job levels in the Kingdom was selected. The study relied on the descriptive analytical approach, and an electronic questionnaire was used as a tool for collecting data. The data was analyzed using the SPSS program. The results of the study concluded that digital transformation has a significant positive impact on achieving development goals in the government sector, by improving operational efficiency and increasing transparency. The study recommended the need to enhance digital transformation strategies in the government sector by investing in digital infrastructure and developing digital skills for workers.